2019
DOI: 10.1177/2010105819868485
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacy among community-dwelling elderly in Singapore: Prevalence, risk factors and association with medication non-adherence

Abstract: Background: Polypharmacy, given its link with drug interactions, potentially inappropriate medications and medication non-adherence, may pose a significant health risk, especially among the elderly. A comprehensive understanding of the epidemiology of polypharmacy is essential for countries facing population ageing and growing chronic disease burden, like Singapore. Objectives: We assessed the prevalence and risk factors of polypharmacy (⩾5 prescription medications) among community-dwelling elderly in Singapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 25 publications
(38 reference statements)
0
7
1
1
Order By: Relevance
“…The UMS is particularly useful for patients with polypharmacy to consolidate their medications to be taken at specific intervals throughout the day. A previous study observed that 14.5% of older Singaporeans had polypharmacy, and those with polypharmacy are less likely to adhere to their medications 25 . Only 21.2% of the PMLs in our study used explicit dosing instructions.…”
Section: Discussioncontrasting
confidence: 53%
“…The UMS is particularly useful for patients with polypharmacy to consolidate their medications to be taken at specific intervals throughout the day. A previous study observed that 14.5% of older Singaporeans had polypharmacy, and those with polypharmacy are less likely to adhere to their medications 25 . Only 21.2% of the PMLs in our study used explicit dosing instructions.…”
Section: Discussioncontrasting
confidence: 53%
“…Moreover, even though they had higher rates of these conditions, they had the lowest rates of screening for chronic conditions, such as cancers, diabetes, hypertension, and high cholesterol (Ministry of Health, 2010). It has been postulated that when there are high rates of undetected or unaddressed chronic health problems, these could lead to greater disease severity and polypharmacy risks (Tan et al, 2019), which potentially increase the overall healthcare utilization. Our results showed several significant interaction effects of mental disorders with specific sociodemographic variables and chronic physical conditions on total costs.…”
Section: Discussionmentioning
confidence: 99%
“…The CI “difficulty with prescribed regimen” may result from several interrelated factors, such as multimorbidities (Maffoni et al, 2020), difficulties in accessing medications or health services, poor health literacy skills (Devine et al, 2018), economic disadvantages (Reiners et al, 2019), and complex treatment regimens (Ayele et al, 2019) characterized by the number of medications needed for daily use (Tan et al, 2019), among others. In studies conducted with people with alcohol use disorder (Silva et al, 2013), people with high blood pressure (Lima et al, 2017), and people with chronic kidney disease on hemodialysis (Paiva et al, 2018), this CI showed high specificity.…”
Section: Discussionmentioning
confidence: 99%